The Effect of Gradient Cooling Behavior on the Microstructure and Mechanical Properties of Al-2at.% Nd Alloy in a Vacuum Environment - Xiangjie Wang; Xinyu Zhang; Wenjie Wu; Shuchen Sun (Crystals)
Al-2at.% Nd alloy with a gradient cooling rate was prepared using a wedge-shaped mold in a vacuum environment. The relationship between gradient cooling behavior and the microstructure and properties of the Al-2at.% Nd alloy was investigated. The stability of the Al11Nd3 phase and the mechanical properties were confirmed through first-principles calculations. The results indicated that as the cooling rate decreased, the transformation of grain morphology in Al-2at.% Nd occurred as follows: a mixture of columnar grains and equiaxed grains→equiaxed grains. The grain size of the alloy increased. Discontinuous skeletal eutectic phases, α-Al and Al11Nd3, formed within the alloy, resulting in a reduction in the number of phase boundaries and grain boundaries. The hardness of the alloy decreased by 25.53%, and this pattern of change closely aligned with the calculated results.